Organopromoted Direct Synthesis of 1,1-Diphenyl-3-arylindanes via Formal [3+2] Cycloadditions of Triphenylcarbenium Tetrafluoroborate with Styrenes - Nakin Surapanich (2018)
© Georg Thieme Verlag Stuttgart.New York-Synlett 2016. A formal [3+2] cycloaddition of triphenylcarbenium tetrafluoroborate with structurally different styrene derivatives has been developed. A combination of benzophenone and Et3N is key for promoting a formal [3+2] cycloaddition of triphenylcarbenium tetrafluoroborate with styrenes affording 1,1-diphenyl-3-arylindanes in moderate to good yields. The reaction mechanism of this transformation is also discussed.